Conclusions - Cassitto, Maria Grazia (La Medicina del Lavoro, 2014)
A number of themes focusing on work-related stress and its consequences are discussed in the selected studies which, although not suitable for a uniform discussion, they all report on situations of practical relevance for workers’ well-being. Ardito et al (1), while reviewing work-related psychosocial risk factors in a highly representative sample of workers from several European Countries, highlighted the main sources of discomfort, taking also gender-related differences into account. Lanfranchi et al (6) and Camerino et al (3) focused on methodologies useful for detecting and possibly taking action on work-related stress in hospital wards and call centres, which equally reflect similarities and differences in sources of distress....